Stream heat budget modeling with HFLUX: Model development, evaluation, and applications across contrasting sites and seasons. (June 2017) - Glose, AnneMarie; Lautz, Laura K.; Baker, Emily A.
Abstract: Process-based models of fluid flow and heat transport in fluvial systems can be used to quantify unknown spatial and temporal patterns of hydrologic fluxes and to predict system response to change. In this study, a deterministic stream heat budget model, the HFLUX Stream Temperature Solver (HFLUX), is developed and evaluated using field studies. Field studies are conducted across two sites with different streamflow rates (0.07 vs 1.4 m 3 /s), and point sources versus diffuse sources of groundwater discharge, to demonstrate model transferability. A winter versus summer comparison at one site suggests latent heat flux should be derived using energy-based methods in summer and mass transfer approaches during winter. For each field study, HFLUX successfully modeled stream temperatures through space and time with normalized root mean square errors of 3.0–6.2%. Model calibration to observed temperature data in order to quantify groundwater contributions and a sensitivity analysis are demonstrated using HFLUX. Highlights: Heat budget model is evaluated across contrasting field sites and seasons. Seasonal considerations when calculating heat fluxes are discussed. Longitudinal stream discharge profiles are auto-generated through calibration.